ACT-14 A FIRST-IN-HUMAN STUDY OF MUTANT IDH1 INHIBITOR DS-1001B IN PATIENTS WITH RECURRENT GLIOMAS. (16th December 2019) - Arakawa, Yoshiki; Mineharu, Yohei; Wakabayashi, Toshihiko; Natsume, Atsushi; Miyakita, Yasuji; Narita, Yoshitaka; Yamasaki, Fumiyuki; Sugiyama, Kazuhiko; Hata, Nobuhiro; Muragaki, Yoshihiro; Nishikawa, Ryo; Shinojima, Naoki; et al.
Abstract: BACKGROUND: WHO grade II/III gliomas frequently harbor isocitrate dehydrogenase 1 (IDH1) mutations, resulting in intratumoral accumulation of oncometabolite D-2-hydroxyglutarate (D-2-HG) and subsequent clonal expansion. DS-1001b is an oral selective inhibitor of mutant IDH1 R132X that was designed to penetrate the blood-brain barrier. METHODS: In this first-in-human, multicenter, phase I study (NCT03030066), eligible patients (pts) with recurrent/progressive IDH1 mutant glioma received DS-1001b twice daily (bid), continuous. A modified continual reassessment method was used for dose escalation. RANO and RANO-LGG criteria were used to assess tumor response. Pts who planned to undergo salvage surgery after developing progressive disease (PD) and who provided informed consent received DS-1001b treatment until surgery. Tumor samples were also obtained from those pts to measure the free form of DS-1001b and D-2-HG levels. RESULTS: Between Jan 2017 and May 2019, DS-1001b (125–1400 mg bid) had administered for 47 pts, and 15 pts were continuing treatment. Maximum tolerated dose (MTD) was not reached. Most AEs were Gr 1–2. Gr 3 AEs were observed in 40% of pts. No Gr 4 or 5 AEs or serious drug-related AEs were reported. One dose limiting toxicity was Gr 3 white blood cell count decreased (1000 mg bid). Of 35 evaluable pts with contrast enhancing gliomas, one, five and 11 achieved complete response, partial response and stable disease (SD), respectively. Of evaluable 12 pts with contrast non-enhancing gliomas, four achieved minor response and eight achieved SD. Peak plasma concentration (Cmax) and area under the curve (AUC) increased dose-dependently. CONCLUSIONS: DS-1001b was well tolerated up to 1400 mg bid with favorable brain distribution, and MTD was not reached. Recurrent/progressive IDH1 mutant glioma pts responded to treatment. Investigation is ongoing to determine the recommended Phase II dose. The latest data will be updated. Funding source: This study was funded by Daiichi Sankyo Co., Ltd.